KISHIK MAKTAB YOSHIDAGI O`QUVCHILARGA ZAMONAVIY EKOLOGIK TA`LIM-TARBIYA BERISH MAZMUNI - Allayarov, M.J. (SCIENCE and SOCIETY, 2023)
This scientific article seeks to increase the systematic technologies of environmental education of young people through proper methods. Moreover, teaching technologies have been developed separately and ways to use them in environmental education of young people are shown.
Keywords: nature; education; environment; student; pedagogy; environmental education; homeland; school